INNOVATIVE EDUCATIONAL AND METHODICAL COMPLEX AS THE BASIS OF INNOVATIVE FORMS OF TEACHING - Umarova Nasiba Erkinovna,; Usmonova Manzura Isakovna, (International Journal of Innovations in Engineering Research and Technology, 2023)
The article is devoted to the problem of design of innovative educational and methodical complex aimed at new forms of organization of educational process in high school with the use of modern information and communication technologies. The author offers a methodical complex on scientific style of speech for foreign students of technical universities of the Russian Federation, which provides the formation of the foundations of the communicative competence of foreign learners in the educational and professional sphere of communication.